2009
DOI: 10.1143/jjap.48.066504
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Water Vapor Heat Treatment for Enhancement of SiOx or SiNx Passivation Layers of Silicon Solar Cells

Abstract: It is shown that in an array of 'bubble domains', interactions will distort each domain from the circular state. The shape will vary with film thickness in such a way that something approximating to 'honeycomb' domains will be stable at large thicknesses. An estimate of the interaction energy density between domains is obtained from an examination of published results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sameshima et al annealed polycrystalline silicon thin film transistors in water vapour to improve their threshold voltage . Ogane et al used water vapour to improve SiN x and SiO x passivation layers for monocrystalline and multicrystalline thin film transistors or solar cells. This work presents for the first time results achieved by annealing of polycrystalline silicon (poly‐Si) thin film solar cells in water vapour.…”
Section: Introductionmentioning
confidence: 99%
“…Sameshima et al annealed polycrystalline silicon thin film transistors in water vapour to improve their threshold voltage . Ogane et al used water vapour to improve SiN x and SiO x passivation layers for monocrystalline and multicrystalline thin film transistors or solar cells. This work presents for the first time results achieved by annealing of polycrystalline silicon (poly‐Si) thin film solar cells in water vapour.…”
Section: Introductionmentioning
confidence: 99%
“…SiNW surface passivation is an even more challenging task due to their small size and the fact that multiple facets with different crystalline orientations are exposed. The various surface passivation layers, such as SiO x and -CH 3 , have been used in previous works [24][25][26][27][28][29][30][31][32]. Scanning tunneling microscopy studies have shown that the CH 3 -terminated Si surface is atomically flat and is terminated by close-packed methyl groups [24].…”
Section: Introductionmentioning
confidence: 99%
“…By applying a controlled in situ passivation of the Si surface with SiO x in the monolayer regime, metallic silicide contaminations at the interface can be effectively reduced down to a sub-monolayer coverage, as was carefully quantified by interface-sensitive hard X-ray photoemission spectroscopy [27]. Ogane et al [28] have proposed high-pressure water vapor heat treatment as a technique for modifying the SiO x passivation layers of silicon solar cells at low temperatures. Zeng and Lin [29] investigated the effect of H 2 O 2 treatment on the electrical and optoelectronic properties of graphene/SiNWs/Si devices.…”
Section: Introductionmentioning
confidence: 99%